The hydraulic architecture of Ginkgo leaves. Issue 9 (28th September 2017) - Carvalho, Mónica R.; Turgeon, Robert; Owens, Thomas; Niklas, Karl J.
Abstract : PREMISE OF THE STUDY: The hydraulics of xylem has been widely studied in numerous species and organ types. However, comparatively little is known about how phloem and xylem are hydraulically coupled or about many of the basic structural properties of phloem (such as conducting cell numbers and conductive areas), which nevertheless have direct bearing on understanding phloem loading and unloading. METHODS: Using a combination of light, epifluorescence, confocal, and transmission electron microscopy, we quantified the hydraulic architecture of Ginkgo biloba leaf laminae and examined the scaling relationships between phloem and xylem in five fully mature leaves. KEY RESULTS: The conductive areas and lengths of sieve cells and tracheids increase basipetally toward the petiole in a manner that is consistent with Münch's pressure flow hypothesis for phloem transport. This trend holds true for individual veins, the sum of conductive areas across all veins at any distance from the petiole, and for individual sieve cells and tracheids. Further, the conductive areas of phloem and xylem are isometrically correlated across the entire vasculature of the leaf lamina. The data for conducting cell areas do not conform with the predictions of the hydraulic models of da Vinci and Murray. CONCLUSIONS: The scaling of Ginkgo lamina hydraulics complies with that observed in leaves of other gymnosperms and most angiosperms and is inconsistent with theoretical models that assume that the volume of transported incompressible fluids is conserved.